Czas w encyklikach Jana Pawła II - Gajewska, Urszula (Stylistyka, 2021)
The article contains the description of temporal relations in encyclicals of John Paul II. Encyclical is an official letter of pope to his church, which main functions are: propaga- tion, elucidation and interpretation basie truths of faith in doctrinal (theological, morał and social) context.As a genre encyclical is on stylistic boundary. It is an apostolic letter, sermon, and from the other point of view scientific tract conceming on theological and morał aspeets.Genre features of encyclicals, transcendental shape of reality described in these texts, character of religious truths (etemal, universal, and forever topical) have influence on temporal relations in analyzed materials.In encyclicals dominates present tense, not in current meaning - but in omnitemporal meaning.Past and futurę tenses play a secondary part, they assist present tense.In encyclical language exists particular all-transitoriness, permanent present, and con- tinuity of current events.